(untitled) (Global Journal of Medical Research, 2023)
Introduction Hearing loss is commonly associated with aging occurring in around 60 of people over the age of 60 The impact of hearing loss can have consequences for the person themselves but can also have collateral effects Family members especially spouses often take on additional responsibilities and family roles can be altered Age-related hearing loss impacts daily life quality of life and the role of caregivers Objective To assess the impact of hearing aids on the quality of life and social participation of hearing-impaired elderly people and their families Methods Systematic literature review using the CINHAL Embase Medline and Pubmed databases with no age restriction